MANAGEMENT OF TRADITIONAL STAKEHOLDERS AND TANTRAYANA COSMOLOGY IN FACING DISEASE OUTBREAK IN BALI - Putri Retnosari; Endah Imawati; I Ketut Sandika (DIA: Jurnal Administrasi Publik, 2021)
In controlling the increase in the spread of COVID-19, the Balinese people, especially Pejeng Village, Tampaksiring District, Gianyar, are guided by the rules of the Traditional Village Council. The community's obedience to the Traditional Village Council and Customary Stakeholders has become a strong foundation in suppressing the spread of the COVID-19 virus. This is evident from the case of covid 19 which has been sloping down from week to week in Pejeng Village, Tampaksiring District, Gianyar. Currently the people of Indonesia and the world are facing an outbreak of the COVID-19 virus disease. This study tries to explore three things, namely the management of traditional stakeholders in coordinating residents to deal with disease outbreaks, the role of Tantrayana teachings in shaping the mentality of Balinese people when facing disease outbreaks, and traditional ceremonies carried out to control Gering Agung. The purpose of this study is to analyze the management of traditional stakeholders in coordinating residents to deal with disease outbreaks, describe the role of Tantrayana teachings in shaping the mentality of Balinese people when facing disease outbreaks and describe traditional ceremonies carried out by the community to control Gering Agung. The approach used in this study is an ethnographic approach. The method used in this study to achieve the target to be achieved by using in-depth interviews which include (a) triangulation, (b) peer debriefing. (c) member check and trial audit. The results of this study indicate that the trust and obedience of the people of Pejeng Village can control disease outbreaks. In addition, the management of customary stakeholders also has a special strategy in guiding residents